Infarct volume after transient middle cerebral artery occlusion (MCAo) can be reduced by attenuation but not by inactivation of c-Jun action - Vogel, Johannes; Weigand, Markus A.; Behrens, Axel; Wagner, Erwin Friedrich; Schorpp-Kistner, Marina; Zimmermann, Manfred; Schenkel, Johannes (Brain research, 2007)
Stroke therapy aims to save penumbral tissue from apoptosis that is activated in response to the ischemic injury. Since the c-Jun transcription factor plays a crucial role in promoting apoptosis, inhibition of its activation might reduce the final infarct size and thus increase functional outcome. To test this hypothesis we made use of four genetically modified mouse lines influencing the c-Jun pathway at various steps. Upon transient middle cerebral artery occlusion for 90 min and 24 h of reperfusion, infarct volume and number of ATF-2-, TUNEL- and cleaved Caspase-3-positive cells were determined in conditional c-Jun knock-out mice (cond. c-Jun), mice overexpressing JunB (JunBtg), mice lacking the phosphoacceptor serines 63 and 73 of c-Jun (JunAA) and in mice overexpressing Bcl-2 (Bcl-2tg). Cond. c-Jun as well as JunAA mice did not show significant differences in the infarct size when compared to their non-mutant controls. By contrast smaller infarct volumes were detected in transgenic mice merely attenuating c-Jun action (JunBtg and Bcl-2tg). ATF-2, TUNEL or cleaved Caspase-3 staining revealed no significant differences between the experimental groups. A complete lack of functional c-Jun might be compensated by other cellular mechanisms, in contrast to its reduced function. Thus, our data suggest that attenuation rather than a complete block of c-Jun action appears to be more promising for therapy of stroke.